2014
DOI: 10.1186/1471-2393-14-179
|View full text |Cite
|
Sign up to set email alerts
|

Transfer to hospital in planned home births: a systematic review

Abstract: BackgroundThere is concern about the safety of homebirths, especially in women transferred to hospital during or after labour. The scope of transfer in planned home births has not been assessed in a systematic review. This review aimed to describe the proportions and indications for transfer from home to hospital during or after labour in planned home births.MethodsThe databases Pubmed, Embase, Cinahl, Svemed+, and the Cochrane Library were searched using the MeSH term “home childbirth”. Inclusion criteria wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
59
1
14

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(77 citation statements)
references
References 28 publications
3
59
1
14
Order By: Relevance
“…The majority of the findings are similar to those already published in studies undertaken in Brazil and other, developed, countries. 4,6,10,12-13, [23][24][25][26] One of the limitations for discussing the present study's findings is the meager publication of quantitative Brazilian data regarding assistance at home so as to compare the results obtained. [10][11]19 In relation to the sociodemographic characteristics, the age range of the majority of the women was below that found in the international studies (between 30 and 34 years old) [26][27][28][29][30] and in another Brazilian study (30-35 years old).…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…The majority of the findings are similar to those already published in studies undertaken in Brazil and other, developed, countries. 4,6,10,12-13, [23][24][25][26] One of the limitations for discussing the present study's findings is the meager publication of quantitative Brazilian data regarding assistance at home so as to compare the results obtained. [10][11]19 In relation to the sociodemographic characteristics, the age range of the majority of the women was below that found in the international studies (between 30 and 34 years old) [26][27][28][29][30] and in another Brazilian study (30-35 years old).…”
Section: Discussionmentioning
confidence: 90%
“…3,28 The systematic review published in 2014, on the other hand, found even lower rates of transfer (0% to 0.2%). 25 Attention is called to the low percentage of cesareans (9.9%) in the total of the sample studied (212) when compared with the Brazilian rate cited above, and with the WHO recommendations that this rate should be below 15%. 51 This finding was similar to that of a study undertaken in Canada, in which 12.0% of the primiparous women, and 1.6% of the multiparous women underwent cesarean section.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…The observed rate of 16.5% in this study is informative and is consistent with rates reported in a recent systematic review of transfers in developed countries (including the United States), in which intrapartum transfer rates ranged from 10 to 17%. 21 The limitations of our study require consideration. First, a major limitation is the inability in the case of planned home births to distinguish between transfers from birth centers and transfers from home.…”
Section: Discussionmentioning
confidence: 93%
“…The definition of normality regarding the latent phase is incongruous and a review of obstetrical textbooks showed that the length of normal latent phase of labour is described as between 2 and 20 hours [12]. Internationally most clinicians continue to use Friedman's original definition of a prolonged latent phase as more than 20 hours for nulliparous and 14 hours in multiparous women [13].…”
Section: Introductionmentioning
confidence: 98%